1986
DOI: 10.1007/bf00122985
|View full text |Cite
|
Sign up to set email alerts
|

On nocturnal wind shear with a view to engineering applications

Abstract: Wind shear data from 14 clear nights with low-level jet development are analysed up to heights of 200 m. Temporal variations of the magnitude of the shear vector and of the power-law exponent p are shown. The frequencies of occurrence of maximum shear and of p are examined and the effect of the product of geostrophic surface wind speed and mean layer temperature gradient on the shear is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…In most cases, the results of validation of mesoscale models against observations revealed that strong near‐surface winds resulted in warm biases in near‐surface temperatures in nighttime CAPs and vice versa (Chiao & Dumais, ; Lee et al, ). An accurate simulation of boundary layer processes affected by LLJs has substantial practical value for transport of urban pollutants, wind power industry, and aviation safety in Yerevan (Storm et al, ; Wittich et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the results of validation of mesoscale models against observations revealed that strong near‐surface winds resulted in warm biases in near‐surface temperatures in nighttime CAPs and vice versa (Chiao & Dumais, ; Lee et al, ). An accurate simulation of boundary layer processes affected by LLJs has substantial practical value for transport of urban pollutants, wind power industry, and aviation safety in Yerevan (Storm et al, ; Wittich et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The nocturnal LLJ is an important mechanism for atmospheric mixing and transport (Stensrud, ) with a large potential to affect aviation (Wittich et al, ), air quality (McNider et al, ; Mao and Talbot, ; Darby et al, ), and the wind energy industry (Storm et al, ). Observational and modelling studies in recent years have indicated that the nocturnal LLJ also plays an important role in the emission and transport of Saharan mineral dust (Knippertz and Todd, ).…”
Section: Introductionmentioning
confidence: 99%
“…The LLJ is a phenomenon typically confined to a vertical wind band of 50 to 200 m thickness (see examples in the studies of Wittich et al , Baas et al , and Prabha et al ) that has been observed and described theoretically for six decades . For some airports with a frequent occurrence of LLJ and high wind speed up to 15 m s −1 , the LLJ is included in forecasts to alert aircraft in the phase of takeoff and landing, where the occurrence of unexpected and strong wind shear and changes of wind direction can be dangerous …”
Section: Introductionmentioning
confidence: 99%
“…In the surroundings of Braunschweig, Germany, the LLJ has beed studied experimentally and numerically by different authors . Typical LLJ events had the wind speed maximum at an altitude around 200 m .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation